Entertainment computing -- ICEC 2013 12th International Conference, ICEC 2013, São Paulo, Brazil, October 16-18, 2013, proceedings - International Conference, ICEC 2013 ((Information systems and applications, incl. Internet/Web, and HCI, 2013)
This book constitutes the refereed proceedings of the 12th International Conference on Entertainment Computing, ICEC 2013, held in Sao Paulo, Brazil, in October 2013. The 13 full papers, 6 short papers, 11 posters presented were carefully reviewed and selected from 75 submissions. In addition to these papers, the program featured 2 demos, 3 workshops, 3 tutorials and 3 art installations, also summarized in this book. The papers cover various topics in the multi-disciplinary field of entertainment computing. An empirical examination of behavioral factors in creative development of game prototypes.- A new chess variant for gaming AI -- Systematic review of game design methods and tools -- Augmented home: integrating a virtual world game in a physical environment -- Debunking differences between younger and older adults using a collaborative virtual environment -- Exploring opponent formats: game mechanics for computer-supported physical games -- Investigating the role of composition conventions in three-move mate problems -- Mappets: an interactive plugin for transmedia machinima on unity3D.- Mobile wars: a mobile GPGPU game -- Step by step: design of an interactive pictorial activity game for teaching generalization skills to children with autism -- Technologically mediated intimate communication: an overview and future directions -- 2D vs 3D visualization and social networks entertainment games: a human factor response case study -- A game design analytic system based on data provenance.- Evaluation of interaction methods for a real-time augmented reality game -- Exercise my game: turning Off-the-shelf games into exergames -- How do people talk with a virtual philosopher: log analysis of a real-world application -- Life-like animation system of virtual firefly based on animacy perception -- A model-driven engineering approach for immersive mixed-reality environments -- A technique to improve freehand sketches of multi-touch interactions -- An artificial emotional agent-based architecture for games simulation -- An enriched artifacts activity for supporting creative learning: perspectives for children with impairments -- Automatic emotional reactions identification: a software tool for offline user experience research -- Evaluating paper prototype for tabletop collaborative game applications -- Initial perceptions of a touch-based tablet handwriting serious game -- Motivation-based game design: a framework for evaluating engagement potential -- Mubil:creating immersive experience of old books to support learning in a museum-archive environment -- Suspended walking: a physical locomotion interface for virtual reality -- Usability evaluation of an application designed for the older adults -- Demonstrating hundreds of AIs in one scene -- Educational: 3D design for mobile augmented reality -- Moment of memory -- The listening walker: interactive sound walk in a virtual city -- VOLTE.